The Effect of the Say-on-Pay Vote in the United States - Iliev, Peter; Vitanova, Svetla (Management Science, 2019)
The Dodd–Frank Act mandated advisory shareholder votes on executive compensation. To isolate the effect of holding a Say-on-Pay vote we use an exemption provided to a group of firms based on their public float. We find that the regulation increased the level of CEO pay and the fraction of performance-linked pay in the companies that had to comply with the new rule. This increase was larger for CEOs with higher ownership and longer tenure. Moreover, the market reacted negatively to the exemption from the Say-on-Pay rule suggesting general support for holding the Say-on-Pay votes. These effects are not present in placebo specifications in previous years or in different groups. This paper was accepted by Lauren Cohen, finance.